A Two-Dimensional Borophene Supercapacitor - Abdi, Yaser; Mazaheri, Ali; Hajibaba, Soheil; Darbari, Sara; Rezvani, Seyed Javad; Cicco, Andrea Di; Paparoni, Francesco; Rahighi, Reza; Gholipour, Somayeh; Rashidi, Alimorad; Byranvand, Mahdi Malekshahi; Saliba, Michael (ACS materials letters, 2022)
This work introduces a new two-dimensional (2D) borophene-based (BB) supercapacitor produced by a chemical vapor deposition method and used in the facile fabrication of nanosupercapacitors (spin-coating on graphite substrates). Structural properties of the as-prepared borophene sheets are fully characterized via AFM, HRTEM, and FESEM, and Raman spectrum of the 2D sheets is scrutinized and discussed, as well as the electrochemical response of the fabricated nanosupercapacitors. A high specific capacity (sCap) of 350 F g–1 is attributed to the device according to the electrochemical tests, that is almost three times higher than previous boron-based supercapacitors and surpasses the best reported 2D materials including graphene. Based on the surface charge-storage mechanism, it is posited that the electrical conductivity and surface area of 2D electrode materials highly affect the performance of the supercapacitor. Simulation studies are also conducted using joint density-functional theory (JDFT), the results of which are in agreement with the reported outcomes of experiments. Application of the newly synthesized 2D BB supercapacitors in the current study is expected to be promising in the energy storage field, inventive class of sensing devices, as well as novel highly sensitive biosensors.